2011
DOI: 10.1016/j.bbmt.2011.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Immune Reconstitution in Recipients of Photodepleted HLA-Identical Sibling Donor Stem Cell Transplantations: T Cell Subset Frequencies Predict Outcome

Abstract: We evaluated an ex-vivo photodepletion technique to selectively deplete graft-versus-host disease (GVHD) alloreacting T cells given to 24 HLA-identical sibling stem cell transplant (SCT) recipients. Donor lymphocytes were activated by 72 hr exposure to irradiated in-vitro expanded recipient T lymphocytes and pulsed with TH9402 photosensitizer. Alloactivated T cells preferentially retaining the photosensitizer were eliminated by light exposure. The photodepletion product showed an inverted CD4+/CD8+ ratio with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
1
31
1
Order By: Relevance
“…Seven patients received a T-cell-depleted graft (protocol 06-H-0248) and 13 received a selectively depleted graft (protocol 07-H-0136). 10 During conditioning, lymphocyte and monocyte counts fell rapidly whereas granulocytes showed a median 3-fold (range, 1.5-6.3) increase over 2 days (related to the dexamethasone administered during the radiation treatment) followed by a rapid decline to zero over the subsequent 5 days ( Figure 1A). All patients established donor myeloid chimerism by day 14, and all 20 patients achieved greater than 95% donor T-cell chimerism at a median of 30 days (range, 14-270 days).…”
Section: Patients Studied and Transplant Outcomementioning
confidence: 98%
“…Seven patients received a T-cell-depleted graft (protocol 06-H-0248) and 13 received a selectively depleted graft (protocol 07-H-0136). 10 During conditioning, lymphocyte and monocyte counts fell rapidly whereas granulocytes showed a median 3-fold (range, 1.5-6.3) increase over 2 days (related to the dexamethasone administered during the radiation treatment) followed by a rapid decline to zero over the subsequent 5 days ( Figure 1A). All patients established donor myeloid chimerism by day 14, and all 20 patients achieved greater than 95% donor T-cell chimerism at a median of 30 days (range, 14-270 days).…”
Section: Patients Studied and Transplant Outcomementioning
confidence: 98%
“…[12][13][14][15][16] However, the contribution of mature donor lymphocytes infused at the time of transplantation has not been fully defined. 17 To explore the influence of immunological characteristics of the donor further, we studied donor lymphocyte counts in a series of patients undergoing HSCT to identify the potential contribution of donor regulatory and conventional T lymphocyte populations to immune recovery and transplant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…31,34 While photo depletion exhibited positive results in haploidentical transplant, 34,35 off-target depletion of CD4 + CM T cells in matched sibling transplants was associated with increased rate of infection and transplant-related mortality. 10 We have shown that adenosine specifically targets alloactivated T cells in mMLR and does not significantly deplete resting memory T cells. Importantly, using adenosine we achieved SD in both haploidentical and matched sibling mMLR (Figure 7).…”
Section: Discussionmentioning
confidence: 84%
“…Photodepletion with a TH9402-based dye failed to improve outcomes in HLA-matched sibling transplants but has shown promise in haploidentical transplants. [10][11][12] An effective, immune modulating strategy for SD which conserves Tregs and can be consistently and easily reproduced in clinical scale has not yet been achieved.…”
Section: Introductionmentioning
confidence: 99%